Pessoas em situação de rua e a questão da moradia : significados, sentidos e implicações na construção da cidadania e das políticas públicas - Pereira, Sandra Mara (2024)
The absence or impossibility of access to housing is a constituent element of “being homeless”. However, housing policy has occupied a marginal space within the policies of care for the homeless population in Brazil. In this sense, this research aims to study public housing policies for homeless people, taking as a starting point the understanding of the senses and meanings attributed to the social phenomenon “homeless” and the issue of “housing”, by managers, policy operators and the homeless– subjects of ongoing research. It is postulated that the symbolic dimension has significant impacts on the constitution of public policies. Therefore, investigating this dimension and how it impacts the development and daily practices of policies is an important exercise in the context of studies on the homeless and public policies. The emergence, still embryonic in the country, of the Housing First model, as opposed to the traditional care model, makes the research carried out even more timely. Within the methodological path, documentary research on policies for the homeless population stands out; carrying out semi-structured interviews with different research subjects and content analysis. As the National Policy for the Homeless Population established in 2009 is a federal regulation that is largely implemented at the municipal level, through co-financing and adherence by municipal managers, there is an important intersection between the national sphere – as a normative construction, and the municipal scope, where care for HP actually takes place. For this reason, the field research strategy was defined as carrying out interviews with subjects who experience the reality of the municipality of Vitória, capital of the state of Espírito Santo, as a possible way of accessing the senses and meanings produced by the subjects. That carry out, operationalize or relate to the homeless policy in their daily practice, as a proxy for a broader context. The research highlighted a disconnect between the social issue of the homeless and the issue of housing: the homeless interviewed stated the centrality of housing in their personal projects, they spoke of the desire to have a house of their own and rebuild their homes; however, housing for the homeless, in the view of professionals and managers, takes on another meaning and appears marginally in the policies of care for this segment